Solaverbascine-A new 22,26-Epiminocholestane Alkaloid from Solanum verbascifolium - Adam, G.; Huong, H. Th.; Khoi, N.H.
Besides solasodine and tomatidine the new alkaloid solaverbascine has been obtained from the leaves of Solanum verbascifolium and identified as (22S :25R)-22,26-epiminocholest-5-ene-3/3, 1613-diol by physical data and direct comparison with synthetic material.
Keywords: SOLAVERBASCINE; EPIMINOCHOLESTANE ALKALOID; SOLANUM VERBASCIFOLIUM